Validação de protocolo de assistência para pessoas com úlcera venosa na atenção primária - Costa, Isabelle Katherinne Fernandes (2013)
People with venous ulcers constitute as an important public health problem, its treatment is onerous and require assistance provided by trained professionals, systematized through protocols, however what lies in the assistance is that the management of this group of people differs from that preconized in the scientific literature, interfering with wound healing and quality of life of affected. In this sense, the construction of a assistance protocol specific to people with venous ulcers (VU) can help professionals of the Family Health Strategy both in patient assessment as and in establishment of quality assistance. Thus, this study aimed to analyse the validity of a multiprofessional assistance protocol for people with venous ulcers in primary care by health professionals using Delphi technique. This is a quantitative study, the methodological type conducted in two steps: first step related to integrative literature review to subsidize the development of the protocol, then these aspects were organized and proposed to the judges of the study through the Delphi technique. The study was initiated after approval by the Research Ethics Committee. The first step was performed between August and September 2012, in the virtual library of health, in the page of the Coordination of Improvement of Higher Education Personnel, of Municipal Health Secretariat and international guidelines of associations and in the subsequent step carried out between September 2012 to January 2013, was performed search by Lattes platform of the National Council of Technological and Scientific Development, in order to identify health professionals in Brazil who act as judges of the instrument and then, via online, the form was submitted to them.The sample for the second step was 51 judges in the first round and 35 for the second round Delphi. The analysis was done by adopting Kappa index ≥ 0.81 and Content Validity Index (CVI)> 0.80. In the first submission for the judges, items that did not reach Kappa and CVI established were: request / realization / test results, demographic data, medical history, risk factors, verification of pain / vital signs / pulse / infection signs / lesion location/ edema and pain treatment. After removal of items which have not obtained Kappa or CVI index established, it was found achieving optimal levels of these index for the categories. In the next step was the ressubmissão of protocol to judges through the Delphi technique in it was found that, of the 15 categories of the protocol, 12 presented higher scores in Delphi 2 phase and the other three categories remained the same Kappa and IVC of the previous phase. As for the average of evaluation requirements of the protocol was found that the scores assigned by the judges were higher in the second phase in nine of the 10 items, remaining the same in only one of the items indicating validity of the instrument before the consensus of the judges. Thus, we accepted the alternative hypothesis in this study, as they were obtained in the second Delphi phase the validity index greater than or equal to the Delphi 1 phase. The formulation of this assistance protocol valid and reproducible will enable a reorganization and redesign of assistance, with standardization of actions and continuity of care for persons with venous ulcers in primary health care